Prevalence of Bovine Trypanosomiases in Tembaro District, Kembata Tembaro Zone, Southern Ethiopia (Global Journal of Science Frontier Research, 2019)
Abstract not found
Keywords: bovine trypanosomiases; prevalence; tembaro; southern ethiopia